Evaluasi Kebijakan, Manfaat, dan Kontribusi Buku Sumbangan Mahasiswa di UPT Perpustakaan Universitas Andalas - Andi Saputra; Fahmi Rizal; Ambiyar Ambiyar (Universitas Sebelas Maret Library, 2025)
Book donation is one of the graduation requirements set at several universities, one of which is Andalas University. This study aims to evaluate the policies, implementation, and benefits obtained by the library from student book donations. This study uses a combination of qualitative and quantitative methods. Data was collected through interviews, literature analysis, and library databases. The data were taken from the last three and processed using descriptive statistical methods. The data analysis process uses Ms. Excel's Pivot Table feature. The results of the study showed that the contribution of donated books was very high, which increased the number of collections at the Unand Library (96.22%). High contribution, not accompanied by the quality of the books obtained. The donated books, as many as 29.2% of the year of publication, are not in accordance with the criteria that have been set. In addition, redundancy or donation of books with the same title reaches 60%. This is due to weak supervision and difficulties for students from certain faculties in obtaining textbooks that are in accordance with their fields of science/major. This study concludes that the high contribution of student-donated books is not accompanied by the quality of the books received. The high level of redundancy leads to a low utilization rate of the collection. The policy for the development of donated book collections must be well planned and formulated, the publicity of the policy must be improved, and the needs of users must be considered.